MONITORING OF QUALITY OF EDUCATIONAL ACHIEVEMENTS: SUBJECT, FUNCTIONS, METHODS - A. V. MALTSEV; A. V. TOMILTSEV (Высшее образование в России)
The article focuses on one type of educational monitoring – monitoring of results of students’ educational achievements. Through a prism of modern processes and innovations in the practice of higher education the authors consider functions of monitoring and its problem zones. The paper emphasizes that there are significant changes in teachers’ role and essential target changes in the student contingent. The authors highlight the importance of taking into account the widely introduced practice of gamification while implementing the monitoring processes in education. The effectiveness of monitoring is stipulated by the effectiveness of information exchange between the monitoring system and management system.